Analyzed Psychological Impact Of An Effect Of Covid-19 On Mental Health On Health Personnel In Hospital Putri Hijau Medan - Dessy Series Ulina Ginting; Santy Siregar; Yolanda Eliza Putri Lubis; Chrismis Novalinda Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
The performance of nurses in hospitals is closely related to reliable, skilled, and professional human resources. Many factors that make it difficult for a person to care for a child are, in fact, length of work, training, motivation, incentives, work environment, and supervision.This research is for the treatment of the factors that is used in the preparation of nurse performance an analytical study with a cross-sectional approach (cross sectional). The research was conducted at Raden Mattaher Hospital, Jambi Province was 406 people and a sample of 261 people. Sampling by purposive sampling. Analyze the data with univariate, bivariate with chi-square test, and multivariate with multiple logistic regression at 95% confidence level ( = 0.05). The results showed that The factors in the development of Rumar General Hospital Raden Mattaher Jambi Province are education and training (p = 0.000), motivation (p = 0.000), incentives (p = 0.020), and supervision (p = 0.002). The variable that has no effect is age (p = 0.584), education (p = 0.786), length of work (p = 0.421), and work environment (p = 0.166). The most dominant variable affecting the performance of nurses is motivation with a value of Exp (B) / OR = 5.626, meaning that nurses who have high motivation have a 5.6 times higher chance of good performance than nurses with low motivation.